Impact of Covid-19 on the Company Arezzo S/A: Analysis of operational and financial cycles (Research, Society and Development, 2023)
Objective: To analyze the consequences that the Covid-19 pandemic is having on the financial result of the Arezzo S/A group during the years 2020 and 2021.Methodology: This is a bibliographical research, using regression and automatic techniques (Sperman), among the indicators of cases by Covid-19, Operational Cycle (OC) and Financial Cycle (CF), as well as analysis of the other indicators that make up the study indicators, Average Storage Period, Average Payment Period, Average Payment Period.Results: Note that the target variable in the CF and CO linear regression had much of its variation explained by the cases of Covid-19. Another relevant factor was the increase in SMEs in the first year of the pandemic. It is believed that the other indicators had their variations softened by public policies of postponing tax payments, as well as postponing creditor payments, as can be seen in the explanatory notes of the company's balance sheets under study. Study Contribution: Shows the impact that the pandemic had on the fashion footwear and sports sector. Although it is a linear regression, it serves as a test for future situations that may happen. The limitation of the study was mainly due to the short interval of data on cases due to Covid-19 and the periodicity of the financial data of the S/A.